El género Tillandsia (Bromeliaceae) en el departamento de Lambayeque, Perú - Ayasta, José (2020)
There are 26 taxa of Tillandsia (Bromeliaceae) that occur in the department of Lambayeque, Peru, of which 12 are registered for the first time, occupying different ecoregions and plant formations, from the low tillandsial to the Jalca. Dichotomous keys for the determination of subgenera, species and varieties are presented and updated data on geographical distribution, altitudinal range, uses and conservation are also provided.